NKX3.1 Activates Expression of IGFBP-3 to Mediate IGF-I Signaling and Cell Proliferation - Muhlbradt, Erin (2009)
NKX3.1 is a homeobox gene that codes for a haploinsufficient prostate cancer tumor suppressor. NKX3.1 protein levels are down regulated in the majority of primary prostate cancer tissues. NKX3.1 expression in PC-3 cells increased IGFBP-3 mRNA expression 10-fold as determined by expression microarray analysis. In both stably and transiently transfected PC-3 cells and in LNCaP cells NKX3.1 expression increased IGFBP-3 mRNA and protein expression. In prostates of Nkx3.1 gene-targeted mice Igfbp-3 mRNA levels correlated with Nkx3.1 copy number. NKX3.1 expression in PC-3 cells attenuated the ability of IGF-I to induce phosphorylation of IGF-IR, IRS-1, PI3-kinase, and AKT. The effect of NKX3.1 on IGF-I signaling was not seen when cells were exposed to long-R3-IGF-I, an IGF-1 variant peptide that does not bind to IGFBP-3. Additionally, siRNA-induced knock down of IGFBP-3 expression partially reversed the attenuation of IGF-1R signaling by NKX3.1 and abrogated NKX3.1 suppression of PC-3 cell proliferation. Thus there is a close relationship in vitro and in vivo between NKX3.1 and IGFBP-3. The growth suppressive effects of NKX3.1 in prostate cells are mediated, in part, by activation of IGFBP-3 expression.